Saving nature under socialism : transnational environmentalism in East Germany, 1968-1990 - Ault, Julia E. (2021)
When East Germany collapsed in 1989-1990, outside observers were shocked to learn the extent of environmental devastation that existed there. The communist dictatorship, however, had sought to confront environmental issues since at least the 1960s. Through an analysis of official and oppositional sources, Saving Nature Under Socialism complicates attitudes toward the environment in East Germany by tracing both domestic and transnational engagement with nature and pollution. The communist dictatorship limited opportunities for protest, so officials and activists looked abroad to countries such as Poland and West Germany for inspiration and support. Julia Ault outlines the evolution of environmental policy and protest in East Germany and shows how East Germans responded to local degradation as well as to an international moment of environmental reckoning in the 1970s and 1980s. The example of East Germany thus challenges and broadens our understanding of the 'greening' of post-war Europe, and illuminates a larger, central European understanding of connection across the Iron Curtain